Identification of potent inhibitors of Leishmania donovani and Leishmania infantum chagasi, the causative agents of Old and New World visceral leishmaniasis - Bilal Zulfiqar; Fabio Antonio Colombo; Juliana Barbosa Nunes; Patricia Ferreira Espuri; Aurea Favero Ferreira; Sujatha Manthri; Manu De Rycker; Marcos Jose Marques; Vicky M. Avery (Communications Biology)
Abstract The drug discovery pipeline for neglected kinetoplastid diseases remains sparse. In particular, the field of leishmaniasis drug discovery has had limited success in translating potential drug candidates into viable therapies. Here, we describe the development of two lead compounds, BZ-1 and BZ1-I, which have potent in vitro anti-leishmanial activity against Leishmania donovani DD8 intracellular amastigotes (0.59 ± 0.13 µM and 0.40 ± 0.38 µM) with corresponding selectivity ( > 33.89 and > 49.12) for differentiated THP-1 cells (Human monocytic cell line), respectively. Further characterization and biological profiling identified that in addition to the activity against L. donovani DD8 (Old World - Indian strain), compounds were active against intracellular parasites from other species and strains of the Old and New World, namely L. donovani (Old World - Sudanese strain) and L. infantum chagasi (New World-South American strain). In vivo evaluation using the hamster model illustrated that the activity observed in vitro was translated in vivo, with outstanding results. Our data suggests that these compounds represent a promising starting point for developing a novel lead series for future anti-leishmanial therapeutics.